Association of food groups and dietary pattern with breast cancer risk: A systematic review and meta-analysis. Issue 3 (March 2023) - Shin, Sangah; Fu, Jialei; Shin, Woo-Kyoung; Huang, Dan; Min, Sukhong; Kang, Daehee
Summary: Background & aims: We conducted a systematic review and meta-analysis of current evidence for the association between food groups, dietary patterns, and breast cancer risk among the Asian population. Methods: This systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. We performed a systematic literature search up to December 2022 in English in the PubMed, Web of Science, Embase, and Cochrane databases. Risk ratios (RRs) with 95% confidence intervals (CIs) were extracted as effect sizes. Publication bias was estimated by two different funnel plot methods. Results: We collected the data from 15 cohort studies and 34 case−control studies meeting the search criteria. The meta-analysis found that the consumption of fruits and, likewise, vegetables were associated with a 29% lower risk of breast cancer, respectively [RR = 0.71 (0.55, 0.93); RR = 0.71 (0.53, 0.95)]. By contrast, no significance was found between meat, soy foods, and green tea consumption and breast cancer risk ( P > 0.05). However, soy protein and isoflavone intake could lower breast cancer risk by 35% and 32%, respectively [RR = 0.65 (0.51, 0.83); RR = 0.68 (0.55, 0.82)]. As for the dietary pattern, high adherence to a healthy dietary pattern and, similarly, to a healthy eating index was associated with a 38% and 51% reduction in breast cancer risk, respectively [RR = 0.62 (0.44, 0.88; RR = 0.49 (0.27, 0.87)], while high adherence to an unhealthy dietary pattern was associated with a 44% increased risk [RR = 1.44 (1.06, 1.96)]. Considering alcohol consumption, a 75% increased risk of breast cancer was found [RR = 1.75 (1.33, 2.30)]. Conclusion: The present meta-analysis found that high intakes of fruits, vegetables, soy protein, and soy isoflavone significantly reduced the risk of breast cancer, while high intake of alcohol had a significantly increased risk. Meat, soy food, and green tea consumption were not significantly associated with breast cancer risk. Considering dietary patterns, high adherence to a healthy eating index and a healthy dietary pattern may reduce breast cancer risk. Conversely, adherence to unhealthy dietary patterns may increase breast cancer risk. However, further studies are needed to confirm the associations between dietary patterns and breast cancer in the Asian population.